Coscinium fenestratum: a review on phytochemicals and pharmacological properties - Bakhtiar, M. Taher; Amri, Mohamad Shahreen; Darnis, Deny Susanti; Abdul Kudos, Muhammad Badri; Shafawi, Anis Natasha; Yazid, Soraya Nur (Springer, 2019)
Coscinium fenestratum has been used in the traditional medicine, especially in the Ayurvedic method of healing as this plant can be found vastly in the Western Ghats of India. The distribution of this plant is concentrated to the Southeast Asiaincluding Sri Lanka, India, Cambodia, Vietnam, Peninsular Malaysia, Sumatra, West Java, Borneo, Northeast of Thailand and Laos. This review is related to the phytochemicals and pharmacological effects of C. fenestratum. The major chemi- cal constituents present in this plant include alkaloids, flavonoids and steroids. The most important bio-active compound is the berberine, which is the most widely studied plant compound. This plant exerts several pharmacological effects including antidiabetic, anticancer, antibacterial, antimalarial, antioxidant, antihy- pertensive, antiulcer, neuroprotector and wound healing activities. This chapter is supported by in vitro and in vivo studies carried out from the year of 1970 to 2016, which are available from PubMed, ScienceDirect, Google Scholar and Scopus.